Treatment of Ulcerative Lesions with Low-level Laser Therapy in a Patient with SARS-CoV-2 - Evllen do Vale Castro; Joao Victor de Paula Freitas; Francisco Artur Forte Oliveira; Lucas Alexandre Maia; Thinali Sousa Dantas; Clarissa Pessoa Fernandes Forte (Wolters Kluwer Medknow Publications, 2024)
Ulcerated lesions have been observed in SARS-CoV-2 patients and their treatment is a challenge. We aim to report the treatment of oral lesions with low-level laser therapy (LLLT) in a patient with SARS-CoV-2. The patient diagnosed with COVID-19 was admitted to the intensive care unit, on mechanical ventilation, and on a nasogastric tube diet that persisted due to oral lesions. Painful ulcerated lesions, clinically diagnosed as viral ulcer, were found on the tongue, palate, labial commissure, and oropharynx during the oral evaluation. An antimicrobial photodynamic therapy with methylene blue and red laser (high energy) was performed, followed by treatment with LLLT with red laser. Significant clinical improvement of the lesions was observed after seven sessions of LLLT, with the oral diet being reestablished. Oral mucosal lesions in patients with COVID-19 are usually symptomatic and with onset after systemic symptoms. LLLT has been used in the management of these lesions, with promising results.